Development of Scientific Attitude Profile Evaluation Using Accumulation, Demonstration, Exercise, Reflection and Create (ADERiC) Learning Models Based Self-Efficacy - Muhammad Syahrul Kahar; Muhammad Fathurrahman; Muhammad Ali; Suswandari; Zaini Fauzi; Arif Darmawan; Suparman (Postgraduate, University of Mataram, 2024)
Learning is a process of interaction between students and their environment so that changes in behaviour for the better occur. This research aims to develop and evaluate a scientific attitude profile evaluation tool that uses the Accumulation, Demonstration, Exercise, Reflection, and Create (ADERiC) Learning Model based on Self-Efficacy. Through a Research and Development (R&D) approach using a 4D model, this research designed and tested this evaluation tool in the context of physics learning. The research results show that the application of the ADERiC model evaluation tool significantly increases students' involvement in the learning process, as well as strengthening their ability to solve problems and develop a positive scientific attitude. Evaluations carried out through the instruments developed indicate an increase in students' self-efficacy along with the use of innovative learning models. These results confirm that the integration of ADERiC in physics learning can facilitate deeper conceptual understanding as well as the practical application of physics, contributing to improving the effectiveness of teaching and learning in schools. This research succeeded in designing and validating an evaluation tool that is able to measure these aspects effectively.